Molecular and kinetic studies of benzene acclimated microbial systems in a surface flow type constructed wetland - Tran, Hau Vuong (College of Engineering, University of the Philippines Diliman, 2014)
Groundwater contamination from leaking underground storage tanks poses risks to human health and the environment. In many of these instances, the contaminant of major concern is benzene, a proven human carcinogen and is a major constituent of gasoline products.The USEPA has set a maximum permissible level of benzene in drinking water at 0.005mg/L. Such a concentration level poses technical and regulatory challenges when it comes to remediation of contaminated sites. In the case of contaminated sites from leaking underground storage tanks,one pressing question would be- What should be an acceptable the remediation goal? Ergo,what does removal of the free product to maximum extent practicable mean?Although some specialized treatment methods may achieve high removal efficiencies upward of 98 percent,the remaining quality can still pose health risks. It is thus necessary to find alternative methods that can improve performance and at the same time are cost effective and require minimum technical expertise.With a view to provide useful information in improving performance of existing biological treatment methods, this research focuses on investigating the bioaugmentation potential of acclimated microbial activities in a surface flow type constructed wetland (CW) setup.The study assesses benzene removal efficiencies of CWs using a commong reed plant Phragmites karka as the main vegetation. Soil used for constructing the wetland system was spiked with benzene weekly for four months to acclimate the benzene degrading bacterium. An unplanted wetland was constructed as a control and to determine the role Phramites karka on benzene treatment.The study assesses benzene removal efficiencies of CWs using a commong reed plant Phragmites karka as the main vegetation. Soil used for constructing the wetland system was spiked with benzene weekly for four months to acclimate the benzene degrading bacterium. An unplanted wetland was constructed as a control and to determine the role Phramites karka on benzene treatment.Results showed that the system with an 8-d hydraulic retention time and high benzene level (66mg/L) in the influent can remove 48% of initial benzene concentration and a stable level at 34 mg/L in the effluent. On the other hand, when the system was operated at low benzene concentration (45 mg/L), treatment efficiency was much higher (99.9%) with effluent reduced to 0.23% mg/L level.Calculations also indicated that the planted constructed wetland performed better, with 17% higher benzene removal than the control. Morover,the result of boxpot analysis shows that differences in benzene concentrations in the effluent were insignificant. These results indicated that treating benzene by CW can be reliable and stable.This research also attempted to isolate and identify indigeneous bacteria from CW set ups in the Philippines and Vietnam. Samples from the rhizosphere and inside the plant root of the CWs were taken and cultured in the laboratory with benzene as the sole carbon source.The samples from both the rhizosphere and inside the root of Vietnam CW had significant benzene degrading capacities while that the Philippine set up showed benzene degradation in the samples taken from the rhizosphere alone. All microbial systems in the CW set ups thrived in aerobic conditions typical in surface flow systems.Sequencing of 16s rRNA identified the isolated strains Enteroabater CedeceadvisaeDSM 4568 Pandoroea pnomena CM25 and Stenotrophomonas maltophilia KHO1.The result of phylogenetic analysis indicates no correlation between three isolated indicating that all three isolated bacteria are of different strains.Growth kinetics was also studied in order to establish the optimum conditions for bacteria growth.Monod kinetic equations involving all three strains for benzene degradation were used to predict benzene concentrations in the effluent. Comparison of measured and predicted benzene concentrations has shown good agreement between these two data sets.